Man-man and the tree of memories a story of dance, magic and liberty! - Badoe, Yaba 1955- (Zephyr, 2023)
"A story of dance, celebration, carnival and slavery, about a family understanding their past to change the future. Set in contemporary Notting Hill, Man-man and his friends are swept up in the exuberant preparations for carnival. But his mother is ill and even as he dances, he calls desperately to the Queen of Revels, as old as time to make her well again. Swept away with his best friend Kareem and sharp-tongued sister Panama, to a place in between, the Queen of Revels plunges Man-man into Africa's past and reveals his family's heritage. As they gather around the sacred Tree of Memories, he witnesses many slaves, captives whose pain and anguish and longing is held by the tree. Man-man understands how this is draining his mother and how he must help her back to the freedom stolen from his ancestors."--Publisher
Keywords: Festivals / Children's fiction; Genealogy / Children's fiction; Generational trauma / Children's fiction; Jamaicans / England / London / Children's fiction; Magic / Children's fiction; Sick / Children's fiction; Time travel / Children's fiction; Fantasy fiction; Kinderbuch